1992
DOI: 10.3758/bf03211627
|View full text |Cite
|
Sign up to set email alerts
|

Filtering versus parallel processing in RSVP tasks

Abstract: An experiment of McLean, D. E. Broadbent, and M. H. P. Broadbent (1983) using rapid serial visual presentation (RSVP) was replicated. A series of letters in one of 5 colors was presented, and the subject was asked to identify the letter that appeared in a designated color. There were several innovations in our procedure, the most important ofwhich was the use of a response menu. After each trial, the subject was presented with 7 candidate letters from which to choose hislher response. In three experimental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

1997
1997
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…The idea that the identity of several items other than the target in the RSVP stream is available is supported by studies requiring the identification of either one or two targets (Botella & Eriksen, 1992;Chun, Bromberg, & Potter, 1994). In an experiment by Botella and Eriksen, participants were required to indicate the identity of a target letter appearing in a specific color by choosing from a list of response alternatives presented at the end of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that the identity of several items other than the target in the RSVP stream is available is supported by studies requiring the identification of either one or two targets (Botella & Eriksen, 1992;Chun, Bromberg, & Potter, 1994). In an experiment by Botella and Eriksen, participants were required to indicate the identity of a target letter appearing in a specific color by choosing from a list of response alternatives presented at the end of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that participants can reliably pick out a target stimulus defined by color when it is presented in a rapid sequence of superimposed stimuli (rapid serial visual presentation, or RSVP, task; Botella & Eriksen, 1992;Chun, 1997;Folk, Leber, & Egeth, 2002;McLean, Broadbent, & Broadbent, 1983). Clearly, in these paradigms, the participants were able to select objects for report on the basis of color.…”
Section: Studies Testing For Direct Selection By Color Without Variatmentioning
confidence: 99%
“…Before discussing previous results on illusory conjunctions in RSVP tasks, I introduce here some terminology adopted from Botella and Eriksen (1992). In a search for a colored target letter appearing among non-colored letter distractors, the color feature defining the target to be reported is the key feature, while the identity of the…”
mentioning
confidence: 99%
“…The patterns of these intrusion errors have been used to infer the processes involved in target performance in RSVP tasks. Different patterns might either reflect different processing strategies employed by the observer (Gathercole & Broadbent, 1984;McLean et al, 1983) or reflect different relative processing times for the independent features involved (Botella & Eriksen, 1992). For instance, a postpattern result may result from the use of an active detect-then-identify search strategy which hypothesizes that processing resources "are devoted to the interrogation ofthe target-defining code to the exclusion ofthe to-be-reported code until a target detection is made" (McLean et al, 1983, p. 184).…”
mentioning
confidence: 99%
See 1 more Smart Citation